Extensão rural e convivência com o semiárido: as transformações de agroecossistemas geridos por mulheres de três territórios pernambucanos - Amorim, Joao Batista Barros de (2023)
This dissertation analyses the on-going material and subjective transformations in agroecosystems of women settled by the land reform, indigenous or quilombolas who have participated in the Program one land two waters (P1+2): Rural Productive Incentive in the Territories of Sertão do Pajeú, Sertão do Moxotó and Agreste Central, in the semiarid region of Pernambuco. From 2018 to 202, the Asa Brasil Network in partnership with the Federal Government mobilized and capacitated women, built and installed calçadão and flooding cisterns, and funded agroecological production projects to expand their consumption and food and nutritional safety. In the various spaces of (re)production of familiar agriculture, these interventions have increased the capacity for collecting and storing rainwater as well as the knowledge regarding the agroecological perspective of living with the semiarid supported by one service of Technical Advice and Rural Extension (ATER) called Monitoring of Socialproductive Activities. Through a multiple study case, seven agroecosystems were analyzed from the extensionist perspective of the Diaconia, the Serta and the Diocesan Caritas in Pesqueira, as well as the P1+2 manager and farmers from three social categories. In addition to the documentary research in a number of organizations, interviews were conducted with extension agents, namely, the manager and the women settled by the land reform, indigenous and quilombolas as well as direct observations of their agroecosystems. The content analysis of empirical findings, combined with secondary data and the theoretical frame support the thesis that, in the Brazilian semiarid, rural extension public services supported by the access to rainwater, novel knowledge and funding to productive projects are capable of improving local production processes, consumption and trade of produce. The assumption is that such changes, mediated by extensionist actions, strengthened the agroecological perspective of living with the semiarid in those territories.